John Locke, A letter concerning toleration, in focus - Horton, John; Mendus, Susan; Locke, John (Routledge, 1991)
Though several editions of Locke's Letter of Toleration art available, the unique value of this volume lies in the fact that it conbines both the text of the Letter and interpretative, critical essays. Several essays are reprints of the most important articles on the Letter, but there is also new material , specially commissioned for the volume and published here for the first time. Given the importance of Locke's Letter on Toleration, this volume will be welcomed by both students and teachers of political philosophy, the history of political thought, as well as philosophy and politics generally.